Impact of Boron Acceptors on the TADF Properties of Ortho-Donor-Appended Triarylboron Emitters - Mubarok, Hanif; Lee, Woochan; Lee, Taehwan; Jung, Jaehoon; Yoo, Seunghyup; Lee, Min Hyung (Frontiers in Chemistry, 2020)
We report the impact of boron acceptors on the thermally activated delayed fluorescence (TADF) properties of ortho-donor-appended triarylboron compounds. Different boryl acceptor moieties, such as 9-boraanthryl (1), 10H-phenoxaboryl (2), and dimesitylboryl (BMes2, 3) groups have been introduced into an ortho donor (D)–acceptor (A) backbone structure containing a 9,9-diphenylacridine (DPAC) donor. X-ray crystal diffraction and NMR spectroscopy evidence the presence of steric congestion around the boron atom along with a highly twisted D–A structure. A short contact of 2.906 Å between the N and B atoms, which is indicative of an N → B nonbonding electronic interaction, is observed in the crystal structure of 2. All compounds are highly emissive (PLQYs = 90–99%) and display strong TADF properties in both solution and solid state. The fluorescence bands of cyclic boryl-containing 1 and 2 are substantially blue-shifted compared to that of BMes2-containing 3. In particular, the PL emission bandwidths of 1 and 2 are narrower than that of 3. High-efficiency TADF-OLEDs are realized using 1–3 as emitters. Among them, the devices based on the cyclic boryl emitters exhibit pure blue electroluminescence (EL) and narrower EL bands than the device with 3. Furthermore, the device fabricated with emitter 1 achieves a high external quantum efficiency of 25.8%.